2023
DOI: 10.1111/sdi.13162
|View full text |Cite
|
Sign up to set email alerts
|

Combined aerobic and resistance exercise in maintenance hemodialysis patients: A meta‐analysis

Abstract: Exercise brings many benefits to patients undergoing maintenance hemodialysis (MHD), but the effect of combined aerobic and resistance exercise remains unclear. English and Chinese databases (PubMed, Cochrane Library, Embase, Web of Science, CNKI, VIP, Wan Fang, and CBM) were searched from inception to January 2023 to retrieve qualified randomized controlled trials. The literature selection, data extraction, and risk of bias assessment of included studies were conducted independently by two reviewers. Meta-ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 73 publications
0
0
0
Order By: Relevance
“…Further, subgroup analysis showed that intradialytic CARE resulted in the amelioration of more evaluated outcomes than non-intradialytic CARE, with the exception of handgrip strength and hemoglobin levels [31]. The authors concluded that CARE is an effective way to improve physical function, aerobic capacity, HR-QOL, and dialysis adequacy in patients on maintenance HD [31].…”
Section: Chronic Effect Of Exercise In Patients With Ckd Undergoing D...mentioning
confidence: 98%
See 2 more Smart Citations
“…Further, subgroup analysis showed that intradialytic CARE resulted in the amelioration of more evaluated outcomes than non-intradialytic CARE, with the exception of handgrip strength and hemoglobin levels [31]. The authors concluded that CARE is an effective way to improve physical function, aerobic capacity, HR-QOL, and dialysis adequacy in patients on maintenance HD [31].…”
Section: Chronic Effect Of Exercise In Patients With Ckd Undergoing D...mentioning
confidence: 98%
“…Meta-analyses of randomized controlled trials (RCTs) have reported that regular exercise training in patients with CKD undergoing dialysis (HD) has benefits in physical function, aerobic capacity, dialysis adequacy, depressive symptoms, and HR-QOL [26][27][28][29][30]. Additionally, a meta-analysis of combined aerobic and resistance exercises (CARE) performed during HD by Liu et al [31] found that CARE improved the peak oxygen uptake; performance on the six-minute walking test; 60-s and 30-s sit-to-stand tests; dialysis adequacy; scores on five (out of eight) domains and the physical component summary for HR-QOL on the Medical Outcomes Study Short Form-36; blood pressure; and hemoglobin levels in patients on maintenance HD compared to those with usual care. Further, subgroup analysis showed that intradialytic CARE resulted in the amelioration of more evaluated outcomes than non-intradialytic CARE, with the exception of handgrip strength and hemoglobin levels [31].…”
Section: Chronic Effect Of Exercise In Patients With Ckd Undergoing D...mentioning
confidence: 99%
See 1 more Smart Citation